2005
DOI: 10.1038/sj.bjc.6602684
|View full text |Cite
|
Sign up to set email alerts
|

p53 immunodetection of liquid-based processed urinary samples helps to identify bladder tumours with a higher risk of progression

Abstract: p53 could help identify bladder tumour cases with a risk of progression from superficial to invasive disease. Semiautomatic, liquidbased cytology (LBC) techniques offer an opportunity to standardise molecular techniques. The aim of our study was to investigate whether LBC could improve p53 immunolabelling, and to assess whether urinary p53 could have a prognostic value. Immunoreactivity for p53 was studied in 198 urine samples after treatment with the Cytyc Thinprep s processor. After antigen retrieval, cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
(32 reference statements)
0
14
1
Order By: Relevance
“…Urinary cytology is less efficient after conservative treatment for bladder cancer, most often near 80% than 100%, and this has stimulated for years the search for biomarkers that could improve accuracy in the follow‐up period. Among many potential markers only few (including Ki‐67, uCyt+, p53 protein and FISH) have been recognized as having an impact in urinary cytology specimens 30,36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Urinary cytology is less efficient after conservative treatment for bladder cancer, most often near 80% than 100%, and this has stimulated for years the search for biomarkers that could improve accuracy in the follow‐up period. Among many potential markers only few (including Ki‐67, uCyt+, p53 protein and FISH) have been recognized as having an impact in urinary cytology specimens 30,36,37 …”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] The sensitivity value obtained in the current series (80.8%) is not very different from those we obtained in previously published series: 83.3% and 64.1%, respectively, in new patients and in those followed after conservative treatment 31 or a global sensitivity of 88.9% in highgrade tumors. 34 The majority of series have achieved pooled sensitivity and specificity results of 42% and 96%, respectively. 35 For comparison, fluorescence in situ hybridization (FISH) using the UroVysion assay allows 72% and 83% pooled sensitivity and specificity results to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that urinary cytology is less efficient after conservative treatment for bladder cancer (most often closer to 80% than 100%) has for years stimulated the search for biomarkers that could improve accuracy in the follow‐up period. Among many potential markers, only a few (including Ki‐67, uCyt+, p53 protein, and UroVysion FISH) have been recognized as having an impact in urinary cytology specimens . In recent years, one of the most promising biomarkers has been p16 INK4a , with particular applicability in gynecopathology in the triage of ASC‐US and LSIL Pap cytology results .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because clinical trial of neoadjuvant chemotherapy in prospective setting showed positive cytology of ascites combined with image scan and serum tumor marker could confirm the diagnosis of advanced epithelial ovarian cancer for potential indication of neoadjuvant chemotherapy,5 use of ascites samples to predict chemotherpeutic response, which can be obtained in less invasive manner, seems to be promising method in those settings. In this study, we investigated p16INK4a expression as a novel prognostic marker for advanced ovarian cancer by immunocytochemistry of ascites using liquid‐based cytology samples providing complementary molecular techniques16, 17 and explored the possibility to predict the chemotherapeutic response and prognosis.…”
mentioning
confidence: 99%